Chemical properties of waste tyre rubber granules - Jusli, Euniza (Trans Tech Publications, 2014)
This research aims to examine the chemical properties of waste rubber tyre granules. Rubber granules were analysed by using X-ray fluorescence to establish its chemical composition. Thermogravimetry and differential thermogravimetric analyses were performed to investigate the relationship between temperature and the minerological compositions of rubber granules to determine its suitability as an aggregate replacement in concrete mix. Fourier Transform Infra-Red (FTIR) indicated that due to the stability of the structures developed in OPC samples, the reactions between the structure bonds are less at the range of 650-1500 cm-1. Scanning electron microscopy (SEM) was performed to examine the physical properties of rubber granule particles and to magnify the bonds between cement and rubber granules in a concrete mix. The results of the SEM analysis showed that carbon, zinc, magnesium, and calcium are the major components of waste tyre rubber granules.